2001
DOI: 10.1046/j.1365-2133.2001.04038.x
|View full text |Cite
|
Sign up to set email alerts
|

alpha6beta4 integrin abnormalities in junctional epidermolysis bullosa with pyloric atresia

Abstract: Junctional epidermolysis bullosa with pyloric atresia (JEB-PA) (MIM 226730) is an autosomal recessive disorder resulting from mutations in the genes encoding alpha 6 beta 4 integrin (ITGA6 and ITGB4). Clinically, it is characterized by mucocutaneous fragility and gastrointestinal atresia, which most commonly affects the pylorus. Additional features of JEB-PA include involvement of the urogenital tract, aplasia cutis and failure to thrive. While most affected individuals have a poor prognosis resulting in death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 48 publications
1
58
1
Order By: Relevance
“…Mice carrying a null mutation of the α6 or β4 subunit do not form HDs and die shortly after birth because of severe blistering of their skin (Dowling et al, 1996;Georges-Labouesse et al, 1996;van der Neut et al, 1996). Similarly, humans who have an autosomal recessive mutation in the genes for either of these integrin subunits exhibit epidermal blistering, the degree of severity depending on the nature of the mutation (Ashton et al, 2001). Because of the perinatal lethality of the α6 and β4 knockout mice, postdevelopmental studies on the effects of the loss of α6β4 were impossible.…”
Section: Discussionmentioning
confidence: 99%
“…Mice carrying a null mutation of the α6 or β4 subunit do not form HDs and die shortly after birth because of severe blistering of their skin (Dowling et al, 1996;Georges-Labouesse et al, 1996;van der Neut et al, 1996). Similarly, humans who have an autosomal recessive mutation in the genes for either of these integrin subunits exhibit epidermal blistering, the degree of severity depending on the nature of the mutation (Ashton et al, 2001). Because of the perinatal lethality of the α6 and β4 knockout mice, postdevelopmental studies on the effects of the loss of α6β4 were impossible.…”
Section: Discussionmentioning
confidence: 99%
“…MEN2A-or MEN2B-inducible genes (type II or type III genes) showed a wide diversity in their possible physiological functions. They include protein kinases (EMK2, PKA-RI), 36,37 cell adhesion molecule (ITGA6), 38,39 microtubule-associated protein (TACC3), 40 protease (neuropsin), 41 and translation initiation factor (EIF4G3). 42 Of 11 type II or type III genes identified, we focused on the STC1 gene because it was reported that it may be involved in the early skeletal development 20 that is affected in MEN 2B patients.…”
Section: Discussionmentioning
confidence: 99%
“…These mice have an extensive blistering of the skin and other stratified squamous epithelium, and lack hemidesmisome formation (8 -10). In patients with pyloric atresia and junctional epidermolysis bullosa, which manifest as cutaneous blistering, mutations in the integrin ␣ 6 or ␤ 4 gene are present, and the severity of the disease is related to the nature of the mutation (11). Hence, it is believed that a primary function of the integrin ␣ 6 ␤ 4 heterodimer is to anchor the basal epithelial cells to the BMZ.…”
Section: Ucous Membrane Pemphigoid (Mmp)mentioning
confidence: 99%